2021
DOI: 10.21037/tau-21-253
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial carcinoma of the renal pelvis with renal vein and inferior vena cava tumor thrombus: case series and literature review

Abstract: Background: Urothelial carcinoma (UC) of the renal pelvis with renal vein and inferior vena cava (IVC) tumor thrombus (TT) was extremely rare. We aimed to explore the clinical and pathological characteristics, diagnosis and treatment of renal pelvis UC with renal vein and IVC TT. Methods: From March 2016 to January 2019, eight patients of renal pelvis UC with renal vein and IVC TT were diagnosed and underwent operation in our hospital. Clinical features, operative details, pathological outcomes, and prognosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Huber et al reported a median survival of 8.9 months for five patients having renal TCC and venous TT; all five of these patients died of their disease [4]. Thus, in spite of our being able to perform a radical nephroureterectomy with minimal complications observed in all patients, our observed median patient survival of 12 months (range: 10 days-24 months) did not appear to differ from these other reports of UTUC with TT [2,4,29,30].…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Huber et al reported a median survival of 8.9 months for five patients having renal TCC and venous TT; all five of these patients died of their disease [4]. Thus, in spite of our being able to perform a radical nephroureterectomy with minimal complications observed in all patients, our observed median patient survival of 12 months (range: 10 days-24 months) did not appear to differ from these other reports of UTUC with TT [2,4,29,30].…”
Section: Discussionmentioning
confidence: 46%
“…Despite aggressive surgical treatment, the prognosis of these patients is very grim, with reported survival being between 6 months and 14 months [2,29]. Huber et al reported a median survival of 8.9 months for five patients having renal TCC and venous TT; all five of these patients died of their disease [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation